Meta-Analysis Study: Is Dental Health Education Effective to Improve Knowledge, Attitude, and Behavior in Adolescents? - Danti Narulita; Danu Aprilianto (Journal of Health Promotion and Behavior, 2022)
Background: Good oral and dental health can help a person chew, talk and socialize with confidence without any discomfort. Teenagers are the next generation of the nation starting from the age of about 12 years to 20 years. At the age of adolescence, deciduous teeth have been replaced by permanent teeth so it is necessary to pay attention to the maintenance of teeth and mouth. This study aimed to analyze the effect of Dental Health Education (DHE) on the knowledge, attitudes and behavior of adolescents.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The search for articles was carried out by considering the eligibility criteria determined using the following PICO model: Population= teenagers, Intervention= DHE (dental health education), Comparison= without DHE, Outcome= Knowledge, attitudes and behavior The article search process was carried out between 2020-2021 using a database from PubMed, Google Scholar, Mendeley and the Wiley Online Library. Based on the database, there were 7 articles that met the inclusion criteria. The analysis was carried out using RevMan 5.3 software.Results: A total of 7 articles reviewed in the meta-analysis showed that Dental Health Education (DHE) increased knowledge (SMD= 0.63; 95% CI= 0.53 to 0.73; p<0.001), attitudes (SMD= 0.41; 95% CI= 0.32 to 0.51; p<0.001) and behavior (SMD= 0.21; 95% CI= 0.11 to 0.32; p<0.001) adolescent.Conclusion: The influence of dental health education increase knowledge, attitudes and behavior among adolescents.Keywords: knowledge, attitude, practice, adolescent, dental health educationCorrespondence:Danti Narulita. Health Polytechnics, Ministry of Health Surakarta. Jl. Letjen Sutoyo, Mojosongo, Jebres, Surakarta, Central Java 57127. Email: danukalih@icloud.com. Mobile: +62821-3329-5468.Journal of Health Promotion and Behavior (2022), 07(03): 197-207DOI: https://doi.org/10.26911/thejhpb.2022.07.03.03